2022
DOI: 10.1002/ajpa.24595
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary history of infectious disease in the ancient Americas and the pathogenic consequences of European contact

Abstract: The increasing availability of next generation sequencing techniques in recent decades has led to new discoveries, and sometimes the redefinition of conventional hypotheses, regarding many complex human‐pathogen evolutionary relationships. These new discoveries are particularly poignant in studies of the Americas, where research into Indigenous ancestry and migration has historically been ignored. As a result, conventional hypotheses regarding the origin of global pathogens like tuberculosis, syphilis, and mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 68 publications
(176 reference statements)
0
9
0
2
Order By: Relevance
“…New paleopathological evidence and recent advancements in genomic sequencing techniques have also generated novel insights into the sustained interactions between humans and pathogens in ancient times. In light of new evidence, Joseph and Lindo (2023) present a redescription of the evolutionary histories of several major infectious diseases in the Americas, highlighting new paleo‐genomic and ‐microbiological data perspectives that now challenge conventional hypotheses about the origins and spread of major pathogenic diseases. As theories of ancient infectious disease patterns often derived from anecdotal evidence from colonial missionary reports, Joseph and Lindo aim to correct the mischaracterization of human–pathogen evolutionary history in the Americas.…”
Section: Critical Insights Of Biological Anthropology In Understandin...mentioning
confidence: 99%
“…New paleopathological evidence and recent advancements in genomic sequencing techniques have also generated novel insights into the sustained interactions between humans and pathogens in ancient times. In light of new evidence, Joseph and Lindo (2023) present a redescription of the evolutionary histories of several major infectious diseases in the Americas, highlighting new paleo‐genomic and ‐microbiological data perspectives that now challenge conventional hypotheses about the origins and spread of major pathogenic diseases. As theories of ancient infectious disease patterns often derived from anecdotal evidence from colonial missionary reports, Joseph and Lindo aim to correct the mischaracterization of human–pathogen evolutionary history in the Americas.…”
Section: Critical Insights Of Biological Anthropology In Understandin...mentioning
confidence: 99%
“…Филогенетический анализ древней ДНК плазмодия, общий размер генома которого составляет около 25 Мб, предполагает два разных пути постконтактного проникновения P. vivax (Grassi et Feletti, 1890) и P. falciparum (Welch, 1897) в Америку. Кроме того, есть указание на связь между современной индийской и европейской линиями P. falciparum (Joseph, Lindo 2022). Болезнь Шагаса вызывает Trypanosoma cruzi Chagas, 1909; даже при лечении специальными препаратами в 10% случаев она приводит к летальному исходу.…”
Section: перспективыunclassified
“…Болезнь Шагаса вызывает Trypanosoma cruzi Chagas, 1909; даже при лечении специальными препаратами в 10% случаев она приводит к летальному исходу. Анализ ДНК южноамериканских мумий указал на наличие трипаносом среди древних популяций еще 9000 л. н. Филогенетические исследования показали, что коренное население Америки впервые столкнулось с T. cruzi как зоонозом от летучих мышей, когда они заселяли Анды и пустыню Атакама (Joseph, Lindo 2022). Первое исследование популяционной геномики круглого червя -власоглава Trichuris trichiura Linnaeus, 1771, вызывающего трихоцефалëз, от которого страдают до 500 000 человек во всем мире (относится к так называемым «забытым тропическим заболеваниям» -neglected tropical diseases), подтвердило происхождение заболевания в Уганде и его последующее распространение с миграцией человека.…”
Section: перспективыunclassified
“…This warning is emphasized by Houldcroft and Underdown (2023), who assert that promulgating broad explanations for Pleistocene population change, such as climate fluctuation, widespread interpersonal conflict, or the advent of agriculture, overlooks the role that infectious diseases played in the past and knowledge we gain from investigating the long‐standing and complex interactions between host and pathogen. Joseph and Lindo (2023) argue that the paucity of knowledge regarding millennia of Indigenous populations' health in the Americas and the emphasis on European contact overshadows and minimizes dynamics associated with widespread and variable patterns of disease—a point emphasized by Honap et al (2023) who found distinct bacterial lineages in the oral microbiomes of pre‐contact Native Americans. In addition, van Doren and Kelmelis (2023) warn that focusing intently on morbidity and mortality during pandemic years masks contributing factors that might play critical roles in the outcome of disease outbreaks.…”
mentioning
confidence: 99%